Delineation of Gambel's Quail Habitat in the Trans-Pecos, Texas - Alfonso Ortega-Sanchez; Louis A. Harveson; Roel R. Lopez; Michael R. Sullins (National Quail Symposium Proceedings, 2017)
Gambel’s quail (Callipepla gambelii) are a common quail species in southwestern states of the United States and the northwestern states of Mexico. In Texas this species occurs in the Trans-Pecos region, are underutilized, and could become an important game bird and source of income for ranchers in the Chihuahuan Desert region of Texas. Salt cedar (Tamarisk spp.), introduced from Asia for ornamental and erosion purposes, is invasive in the western part of the Rio Grande corridor that generally creates monocultures that choke out the native vegetation of the region. Knowing this, the objectives of this study were to: (1) delineate salt cedar and native riparian habitats along the Rio Grande corridor in the Trans-Pecos; (2) evaluate those habitats based on the known distribution of Gambel’s quail in the Trans-Pecos; and (3) estimate the amount of suitable habitat for Gambel’s quail in Trans-Pecos, Texas. Although dominant along the Rio Grande, native riparian vegetation was more prevalent than salt cedar communities when combining primary creeks in all counties. Brewster County was the area with a higher percentage of salt cedar occurrence (21.2%) vs. native riparian vegetation (78.8%). The largest extension of salt cedar occurred in Presidio County with an extension of 6,656.3 ha but this only represented 12.7% of our analyzed area. Hudspeth County had an occurrence of salt cedar of 2,905.2 ha representing 6.8% of the estimated riparian area of the Rio Grande corridor in this county. El Paso County’s total urban area-agricultural fields area is a total of 90,682.9184 ha.
Keywords: Callipepla gambelii; Gambel’s quail; GIS; habitat; riparian vegetation; salt cedar; Texas; Trans-Pecos